Optimization of citric acid and cassava starch-based edible coating formulation on pineapple(Ananas comosus L. Merill) slices - Anyayahan, Angeli Anne Joyce Panghulan (UP College of Home Economics, 2012)
ABSTRACT Fresh pineapple slices were minimally processed and packaged with an acid-based edible coating to preserve the quality of the fruit. The slices were dipped in varying citric acid (CA) concentrations (0.5%, 1% and 2%) and were further immersed in varying cassava starch (CS) suspension (1%, 2% and 3%) before storage at low temperature. The slices were evaluated for physico-chemical, sensory and microbiological properties at pre-determined storage time intervals. Percent weight loss, color and vitamin C content were determined and statistical analysis showed that the color parameter L* showed significant difference (P<0.05) among the treatments. Regression analysis revealed that at 1.8% CA and 2.8% CS and beyond, the slices were observed to have higher L* values after 2 weeks of storage which may imply preservation of desirable color. Sensory evaluation of stored pineapple slices showed significant differences (P<0.05) in acceptance of Aroma over time. Microbiological assessment on the other hand revealed that the acid-based edible coating was able to maintain the total plate count and yeast and mold count of the coated samples within the microbiological standards for at least two weeks at low temperature.